2 Samuel and the Architecture of Poetic Justice - Kozlova, Ekaterina E. (Journal of Hebrew Scriptures, 2022)
The so-called Succession Narrative abounds in references to locales and architectural structures used by royals and their aides to their advantage in matters of private and national interests. This article considers two episodes, which feature individuals lamenting near entrance ways: in 2 Sam 13:1–20 Tamar, David’s daughter, laments on either side of the door to Amnon’s private quarters; and in 2 Sam 18:33–19:1–4, David laments over the city gate. Using studies on the intersection of place, ideology, and behaviour and analysing the bolted door and the chambered gate within their immediate contexts and a wider narrative space (i.e., the Absalom crisis), this article discusses the role these structures play in the construction of David’s reign.